Effects of tiletamine-zolazepam vs. propofol on peri-induction intraocular pressure in dogs: A randomized, masked crossover study - McIver, Katharine A.; Boveland, Shannon D.; Clark-Price, Stuart C.; Hofmeister, Erik H. (Frontiers in Veterinary Science, 2023)
Introduction Anesthesia induction agents have the potential to cause severe ocular side effects, resulting in lasting damage to the eye. Objectives The purpose of this study is to determine the effects of tiletamine—zolazepam on IOP compared to propofol when they are used as an induction agent in normal healthy dogs. Methods Twenty healthy adult client owned dogs weighing 22.2 ± 7.6 kg were selected for the study. In a randomized order, all dogs received tiletamine-zolazepam 5 mg/kg IV or propofol 8 mg/kg IV titrated to effect without premedication. Washout between each treatment was at least seven days. IOP measurements were obtained at four time points: baseline, post-induction, post-intubation, and after recovery using applanation tonometry. No additional procedures were performed. After normality of the data was determined, a linear mixed model was built with time, eye, treatment and all interactions of those variables as fixed effects and subject as a random effect. Results There was no significant difference for age, body weight, drug dose, baseline IOP, and recovery IOP between treatments. Average IOP measurements remained within the normal range of 15-25 mmHg at these time points. However, IOP was significantly less elevated by the tiletamine-zolazepam treatment vs. propofol at the post-induction (mean difference: −4.7 ± 4.6 [95%CI −6.8 to −2.5]) and the post-intubation (mean difference: −4.4 ± 4.6 [95%CI −6.5 to −2.2]) time points. Clinical significance Dogs receiving tiletamine-zolazepam for anesthetic induction had a significantly less elevated IOP at induction and intubation compared to dogs receiving propofol.